EFL students’ voices on the use of Discord in a critical listening course - Mubarok, Harir; Lestari R, Kenny Shania; Ramadhan, Iqbal (Journal of English Language Teaching and Learning (JETLE), 2025)
The increasing popularity of the internet has prompted people to embrace digital platforms for language acquisition. Language learning environments now exist in both physical classrooms and virtual spaces. Therefore, listening skills, which are an important component of language proficiency, especially in higher education can be effectively taught through a medium such as Discord, a new and useful digital learning tool. The primary aim of this study is to explore students’ voices regarding the use of Discord to enhance critical listening proficiency. To gather meaningful data, a descriptive qualitative design was employed using instruments such as classroom observation checklists, field notes, and Focus Group Discussions (FGD). The study involved 20 students enrolled in the International Class Program at Maulana Malik Ibrahim Islamic State University Malang. The findings revealed that Discord facilitates the organization of systematic materials, provides features supporting both offline and online learning, encourages the design of new interactive educational activities, and enables immediate responses that promote dynamic discussions. The implication of this study suggests that Discord can be adopted as an effective supplementary platform for developing students’ listening skills and fostering collaborative learning in digital language classrooms.